(untitled) (Journal of Plant Disease Sciences, 2023)
Maize ( L.) is one of the most significant cereal crops and holds a Zea mays significant position in global agriculture because of its high potential for yield and strong market demand. This study focuses on Turcicum leaf blight, a disease that severely affects maize crops and can result in yield losses of 25–90%. The disease symptoms were identified and the causative fungus was isolated and confirmed as growth varied on several cultural media, and the isolated pathogen showed a range of morphological and colony characteristics. An excellent growth of mycelium (90 mm) was observed on PDA and Oat meal agar. Minimum mycelial growth (66.03 mm) was recorded on Subourauds agar.